2020
DOI: 10.1111/cas.14299
|View full text |Cite
|
Sign up to set email alerts
|

Claspin overexpression is associated with high‐grade histology and poor prognosis in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is one of the most common human cancers. We previously reported that claspin is a key regulator in the progression of gastric cancer, and it likely plays an important role in cancer stem cells of gastric cancer. However, the significance of claspin in RCC has not been examined. First, we analyzed the expression and distribution of claspin in 95 RCC cases by immunohistochemistry. In the nonneoplastic kidney, the staining of claspin was either weak or absent, whereas RCC tissue showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
(94 reference statements)
1
21
0
Order By: Relevance
“…Several reports have shown that CD44 is expressed in various types of tumors and in the livers in patients with nonalcoholic steatohepatitis (NASH). Moreover, soluble CD44 levels are increased in the serum of patients with colorectal cancer and NASH (Gurzu, Kobori, Fodor, & Jung, 2019;Kobayashi et al, 2020;Masson et al, 1999;Patouraux et al, 2017). Because CD44 was expressed in renal tubules immediately after I/R injury without fibrotic lesions in the current study, detection of CD44 in liquid biopsies using urine or serum samples after kidney injury may have applications in predicting the AKI to CKD transition.…”
Section: Discussionmentioning
confidence: 74%
“…Several reports have shown that CD44 is expressed in various types of tumors and in the livers in patients with nonalcoholic steatohepatitis (NASH). Moreover, soluble CD44 levels are increased in the serum of patients with colorectal cancer and NASH (Gurzu, Kobori, Fodor, & Jung, 2019;Kobayashi et al, 2020;Masson et al, 1999;Patouraux et al, 2017). Because CD44 was expressed in renal tubules immediately after I/R injury without fibrotic lesions in the current study, detection of CD44 in liquid biopsies using urine or serum samples after kidney injury may have applications in predicting the AKI to CKD transition.…”
Section: Discussionmentioning
confidence: 74%
“…In some up-to-date articles, it has been reported to increase resistance to various therapies in lung and ovarian cancers (Choi et al, 2012;Ito et al, 2018). In addition, CLSPN coexpresses with PDL-1, CD44, EGFR, p53 and acts as a poor prognosis fact in renal cell carcinoma (Kobayashi et al, 2020). Besides, some researches showed that overexpressed CLSPN leads to solid tumors poor prognosis and progression (Allera-Moreau et al, 2012;Wang et al, 2017;Kobayashi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of CLSPN may induce genomic instability and cause cancer progress. More importantly, high CLSPN expression is linked to the poor prognosis and cancer promoted effect in bladder cancer, renal cell carcinoma, breast cancer, and lung cancer (Sato et al, 2012;Li et al, 2013;Choi et al, 2014;Kobayashi et al, 2020). However, the role of CLSPN in PCa is still to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that patients with higher T grade, advanced tumor stage, vein invasion and inferior prognosis were likely to exhibit stronger CLSPN staining. In addition, CLSPN activates the AKT signaling pathway and is co-expressed with several known tumorrelated genes, such as programmed death ligand-1, epidermal growth factor receptor et al [47]. Previous studies have reported that KIF23 is a kinesin-like motor protein that plays a significant role in cytokinesis and has two splice variants, KIF V1 and KIFV2, which are overexpressed in HCC samples but were not detected in nontumor tissues.…”
Section: Discussionmentioning
confidence: 99%